Efektivitas Permainan Teka-Teki Silang Terhadap Pengenalan Kosakata Bahasa Inggris Anak Usia 5-6 Tahun Di Taman Kanak-Kanak Uswatun Hasanah Kota Padang - Aulia, Hasnatul; Marlina, Serli (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The motivation for this study stems from the fact that the teacher only introduces English vocabulary through picture guessing games, which in reality only teach basic vocabulary definitions. The purpose of this study was to determine how successful crossword puzzle games are at teaching English vocabulary to children between the ages of 5 and 6 at Uswatun Hasanah Kindergarten in Padang City. This kind of study uses a one-group pretest-posttest design model and is quantitative with a quasi-experimental design. According to the study's findings, crossword puzzles helped children at Uswatun Hasanah Kindergarten in Padang City, Indonesia, aged 5 to 6, recognize English words